1997
DOI: 10.1117/12.281200
|View full text |Cite
|
Sign up to set email alerts
|

<title>Imaging of surface plasmons with a near-field microscope</title>

Abstract: Imaging of surface plasmon polaritons (SPP's) with a photon scanning tunneling microscope (PSTM) combined with shear force feedback is experimentally investigated. A contrast correction factor, that accounts for spatial frequency filtration performed by an uncoated fiber tip of the PSTM (when detecting the SPP intensity distribution), is introduced and evaluated from the measurements of a standing wave interference pattern formed by two counterpropagating evanescent waves, that are generated by total internal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
25
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 0 publications
7
25
0
1
Order By: Relevance
“…21 Such an approach allows one to circumvent the very complicated problem of SPP scattering by surface inhomogeneities and concentrate the efforts on various phenomena that were experimentally observed in ͑multiple͒ elastic SPP scattering. 4,8,[11][12][13]16 In this paper, we present numerical simulations of elastic SPP scattering by randomly located and specifically configured isotropic pointlike scatterers, and compare our calculations with the previously reported and additionally obtained experimental results. The paper is organized as follows.…”
mentioning
confidence: 69%
See 2 more Smart Citations
“…21 Such an approach allows one to circumvent the very complicated problem of SPP scattering by surface inhomogeneities and concentrate the efforts on various phenomena that were experimentally observed in ͑multiple͒ elastic SPP scattering. 4,8,[11][12][13]16 In this paper, we present numerical simulations of elastic SPP scattering by randomly located and specifically configured isotropic pointlike scatterers, and compare our calculations with the previously reported and additionally obtained experimental results. The paper is organized as follows.…”
mentioning
confidence: 69%
“…The first assumption is justified by the experimental observations showing the appropriate interference patterns, whose periods corresponded to the interference between the incident and scattered SPP's, 4,[11][12][13]16 and signal ͑tip-surface͒ distance dependencies, that exhibited exponential behavior related to the evanescent decay of the SPP field. 8 In addition, recent theoretical results for an individual surface defect indicated that the elastic SPP scattering becomes dominant over the scattering out of the surface plane in the case of resonant SPP scattering. 18 The second assumption is primarily based on the circumstance that wellpronounced parabolic interference fringes were observed with SPP scattering by individual defects.…”
Section: Model For Elastic Scattering Of Surface Polaritonsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, one has to determine the transfer function of the fiber tip used ͑assuming that it can be considered as a passive probe 29 ͒, which is a challenging problem itself. 43 Taking into account that, for the spatial period of ϳ300 nm of the intensity interference pattern, the contrast correction factor is ϳ2, 43 one can deduce that the enhancement corresponding to the experimental images is at least 40 times. Alternatively, one can consider the imaging of bright spots with uncoated fiber tips that has been modeled theoretically.…”
Section: Resultsmentioning
confidence: 99%
“…1 were measured by using an illumination wavelength ¼ 632:8 nm and for two metallic smooth¯lms in order to determine the resonant excitation angle for the corresponding SPP. 52 The shape of the ATR curve was quantitatively described by using the three layer Fresnel equation. The calculated curve allows one to extract the dielectric constant of the¯lm from a¯t to the measured resonance spectrum.…”
Section: Far-field Characterization Of Spp Propertiesmentioning
confidence: 99%